Rencana Pengembangan Peternakan Terpadu di Gampong Klieng Cot Aron, Aceh Besar: Respons Terhadap Perubahan Lingkungan dan Ekonomi Lokal - Zuraidi, Evalina; Irwansyah, Mirza; Caisarina, Irin (Universitas Syiah Kuala, 2024)
This paper reports on a community service activity conducted in Gampong Klieng Cot Aron, Aceh Besar Regency, to assist the local community in formulating a development plan for integrated livestock farming. This initiative responds to the environmental and local economic changes resulting from the construction of a toll road and the expansion of the brick industry. Methods such as observation, interviews, and Participatory Rural Appraisal (PRA) were employed to gather data and input from the community. The findings indicate a shift in livestock farming patterns from exclusive to inclusive and semi-inclusive systems. The proposed development plan includes an integrated livestock farming concept focusing on site selection and livestock pen design, waste management, enhancement of farmers' knowledge, and marketing of livestock products. Furthermore, land integration with the cultivation of elephant grass, corn, and sweet potatoes is suggested to support economic diversification and ensure a sustainable feed supply. Supporting facilities, such as a livestock service center and the establishment of a village-owned enterprise (Badan Usaha Milik Gampong-BUMG), are also proposed to strengthen the village economy.